Thanksgiving : why we celebrate it the way we do - Hintz, Martin; Hintz, Kate (Mankato, Minnesota : Capstone Press, 1996)
Describes the origins of thanksgiving and how we celebrate the holiday.
Includes bibliographical references and index.
Keywords: Thanksgiving day -- Juvenile literature